Secagem convectiva de minério de manganês - Hidalgo, Letícia Ferraresi (2025)
From mine extraction to exportation, manganese ore fines undergo processes that influence the water content and, consequently, their agglomeration. High moisture content in ores impairs handling and shipping operations, although some residual moisture can allow the agglomeration of these fines, minimizing their generation and consequent losses or environmental risk during transfers. Given the production scale of mining companies, preliminary information regarding the characteristics of minerals and the viability of drying processes can facilitate the enhancement or readjustment of production lines, resulting in significant savings in time and resources. In this sense, the present work aimed to evaluate the drying kinetics of clusters produced by manganese ore fines in an oven and fixed bed, in order to obtain kinetic coefficients for the processes that guide issues in the mining industry. For this purpose, physical and chemical characterizations of the material were carried out, as well as drying tests under different operational conditions. The results were evaluated according to the kinetic curves and drying rates, in order to reach parameters that describe the convective and diffusive processes. For the experimental conditions of this work, the manganese ore drying occurred under the stages of heating, constant rate and falling rate period. Structure influences due to the moisture level, the diffusive medium size, the temperature and the speed of the drying air in the process were reported. For a moderate moisture reduction, the manganese ore could be dried during only the constant rate period, for almost all experimental conditions evaluated, in order to reach the necessary transport condition, what indicates lower energy consumption and cost for drying equipment installation on mineral processes.